A Conspiração da Vaca:: Comunicação e Sustentabilidade à luz de Cowspiracy (2014) - Germiniano de Azevedo, Hercilene (Revista de Comunicação Dialógica, 2026)
The documentary Cowspiracy: The Sustainability Secret (2014), directed by Kip Andersen and Keegan Kuhn, presents an investigation that seeks to understand who the main contributors to the planet’s environmental degradation are and what measures are being taken to reverse this situation. The film stems from Andersen’s personal concern; worried about climate change, he adopts sustainable habits in his daily life. However, as he delves deeper into his research, the director realizes that his individual actions, no matter how well-intentioned, had very little practical impact when compared to the damage caused by the livestock industry to the planet. Keywords: Sustainability; Environmental Degradation; Animal Agriculture, Climate change